On the Mazur-Ulam problem in fuzzy anti-normed spaces - Abrishami-Moghaddam, Majid (International Journal of Applied Mathematical Research, 2014)
The aim of this article is to proved a Mazur-Ulam type theorem in the strictly convex fuzzy anti-normed spaces.Keywords: Fuzzy anti-normed space, Mazur-Ulam theorem, strictly convex.